2014
DOI: 10.1039/c4py00190g
|View full text |Cite
|
Sign up to set email alerts
|

The effect of LiNTf2 on the propagation rate coefficient of methyl methacrylate

Abstract: LiNTf2 catalyses the propagation step of methyl methacrylate radical polymerization but this catalysis hinders stereocontrol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 35 publications
(52 reference statements)
2
46
0
Order By: Relevance
“…56,60,62 Addition of ZnCl 2 to reaction mixtures of MMA in N,N-dimethylformamide (DMF) increased the rate of polymerization relative to the control solution 2.43 at a Lewis acid:monomer ratio of 0.15:1, while the presence of AlBr 3 in similar reaction mixtures at a salt:monomer ratio of 0.35:1 improved the rate of reaction approximately 4.23 in comparison to the control mixture. 62 As mentioned previously, multiple studies have found improvements in the reaction kinetics and product properties for radical polymerizations containing LiOTf and LiTf 2 N. [56][57][58][59][60] The improvements in the radical polymerization kinetics in these reactions have been attributed to both electronic and electrostatic factors. [56][57][58][59][60]62 For the ethylene oxide methacrylate polymerizations, the addition of the salt was associated with a corresponding shift in the position of the CAH vinyl stretching peak to higher wavenumbers.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…56,60,62 Addition of ZnCl 2 to reaction mixtures of MMA in N,N-dimethylformamide (DMF) increased the rate of polymerization relative to the control solution 2.43 at a Lewis acid:monomer ratio of 0.15:1, while the presence of AlBr 3 in similar reaction mixtures at a salt:monomer ratio of 0.35:1 improved the rate of reaction approximately 4.23 in comparison to the control mixture. 62 As mentioned previously, multiple studies have found improvements in the reaction kinetics and product properties for radical polymerizations containing LiOTf and LiTf 2 N. [56][57][58][59][60] The improvements in the radical polymerization kinetics in these reactions have been attributed to both electronic and electrostatic factors. [56][57][58][59][60]62 For the ethylene oxide methacrylate polymerizations, the addition of the salt was associated with a corresponding shift in the position of the CAH vinyl stretching peak to higher wavenumbers.…”
Section: Discussionmentioning
confidence: 93%
“…62 As mentioned previously, multiple studies have found improvements in the reaction kinetics and product properties for radical polymerizations containing LiOTf and LiTf 2 N. [56][57][58][59][60] The improvements in the radical polymerization kinetics in these reactions have been attributed to both electronic and electrostatic factors. [56][57][58][59][60]62 For the ethylene oxide methacrylate polymerizations, the addition of the salt was associated with a corresponding shift in the position of the CAH vinyl stretching peak to higher wavenumbers. 60 As the presence of similar phenomena in H-bonding systems results in increased monomer reactivity, the increase in the rate of propagation was attributed to favorable electronic redistributions within the vinyl group as a result of interactions between the C@O group and the Li 1 cation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…87,88 Indeed, it is interesting to note that in the gas phase the interaction energy between the methyl radical and Li þ is over 50 kJ mol À1 . 87 More recent work has confirmed that Li þ exerts a modest stabilizing effect on unimeric MMA radicals, 89 although it is unclear to what extent this stabilization may simply reflect polar effects.…”
Section: Important Features Of Radical Reactivitymentioning
confidence: 94%
“…89 Although LiNTf 2 was found to be ineffective for isotactic control experimentally, these calculations suggest that under normal polymerization conditions, terminal-penultimate chelation infers a modest selectivity preference of around 5 kJ mol À1 for linear pro-meso conformations of the polymer terminus compared with helical pro-racemo configurations. 89 If this level of selectivity was retained in the respective meso and racemo transition states, it would result in a highly isotactic-rich polymer at 25 C (m ¼ 90%).…”
Section: Does the Chelate Favor Meso Propagation?mentioning
confidence: 97%